Prophylaxis of lymphocele formation after kidney transplantation via peritoneal fenestration: a systematic review - Mihaljevic, André Leopold; Heger, Patrick; Abbasi Dezfouli, Sepehr; Golriz, Mohammad; Mehrabi, Arianeb (Transplant international, 2017)
Lymphocele formation after kidney transplantation is a frequent complication which causes pain, secondary graft loss, rehospitalizations and reoperations. Therefore, prophylaxis of lymphocele formation is of utmost importance. To assess the effectiveness of peritoneal fenestration in renal transplantation to prevent lymphocele development. A systematic literature search was conducted combined with hand-searches on lymphocele prevention following renal transplantation using peritoneal fenestration. A qualitative and quantitative analysis of included trials was conducted. We identified three trials including 414 patients and 437 transplantations which studied peritoneal fenestration. Only one randomized controlled trial was identified. Critical appraisal uncovered a number of methodological flaws, predominantly in the nonrandomized studies. Most importantly endpoint definitions varied among trials, selection bias was high and interventions and follow-up were not standardized. Meta-analysis of the included trials showed a significant reduction of clinically symptomatic lymphoceles (OR: 0.23, 95% CI: 0.09-0.64, P = 0.005) and overall postoperative fluid collections (OR: 0.49, 95% CI: 0.28-0.88, P = 0.02) without a significant increase in other surgical complications. Although peritoneal fenestration is a promising technique to reduce lymphocele formation, only few studies have investigated this technique so far. Given the low methodological quality of included trials, more studies are necessary to evaluate the effectiveness and the risks and benefits of this technique.
Gesehen am 31.10.2018